1996
DOI: 10.1002/elan.1140080705
|View full text |Cite
|
Sign up to set email alerts
|

Stand for high pressure electrochemical measurements

Abstract: The complete stand for a high pressure electrochemical experiment (up to 0.8 GPd), construction of the electrochemical cells and the high pressure chamber is presented. The procedure of a high pressure voltammetric experiment is described with some practical advice on how to prepare and maintain the electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Detailed accounts of these results have been produced previously and readers are pointed to the following articles for a more thorough overview of these early experiments [3, 4, 12, 22 ± 29]. However, it has since been observed that these early studies often lacked reproducibility and accuracy [23], which can be attributed to the practical difficulties and the complicated experimental apparatus [30] required to record accurate measurements at high pressure.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Detailed accounts of these results have been produced previously and readers are pointed to the following articles for a more thorough overview of these early experiments [3, 4, 12, 22 ± 29]. However, it has since been observed that these early studies often lacked reproducibility and accuracy [23], which can be attributed to the practical difficulties and the complicated experimental apparatus [30] required to record accurate measurements at high pressure.…”
Section: Introductionmentioning
confidence: 93%
“…Golas and co-workers [30] have recently described a complete apparatus for voltammetric measurements at high pressure (up to 0.8 GPa, or ca. 8 kbar) and provided practical advice on how to prepare and maintain the electrodes used in such experiments [30,31,55].…”
Section: Three Electrode Cellsmentioning
confidence: 99%
See 3 more Smart Citations